Alternative views and assessments : The Macapagal-Arroyo presidency and administration, records and legacy - Abueva, Jose V. (Quezon City : University of the Philippines Press, 2004)
v.2, xxii, 636 page
Keywords: Philippines -- Politics and government, 2001-2004.